Implementation of Illiteracy Eradication Program in Katoi District North Kolaka, Indonesia (EDUCATIO : Journal of Education, 2017)
Implementation of Illiteracy Eradication Program in Katoi Sub-District, North Kolaka District, under the guidance of Dr. Azhari, S.STP., M.Si as the supervisor I and Mr. Arafat Yasir, S.Pd.I., M.Si As mentor II. This study aimed to find and describe Implementation of Illiteracy Eradication Program in Katoi District North Kolaka, Indonesia. This research was a research with descriptive qualitative type, informant in this research as many as fifteen people. Data collection techniques were direct observation and direct interview. As for data analysis used Data Reduction, Data Presentation, and Drawing Conclusion. The results of this study indicated that the funds from the government were insufficient for the implementation of this Illiteracy Eradication program. The target of the Illiteracy Eradication program was in line with its objectives. Residents of learning who follow this illiteracy eradication program had been in accordance with the targets set by the implementer of Literacy Eradication program. While the selection of tutors and organizers should not be absolutely appropriate to the criteria established by the government. The election took precedence that had a high social spirit and willing to serve for the community, this was related to the implementation of illiteracy programs that were non-formal.